Cognitive implications of nominalizations in the advancement of scientific discourse - Bello, Iria (International Journal of English Studies, 2016)
Nominalizations are well-known features of scientific writing. Scholars have been intrigued by their form and by their functions. While these features have been widely studied, the cognitive side of nominalizations in scientific texts still needs further attention. Nominalizations contribute to the advancement of discourse and at the same time add abstraction to the processes they convey and make them become more reified in the eyes of the reader. They are not mere verbal transformations as they change completely the cognitive configuration of the process they express. With examples retrieved from the astronomy subcorpus (CETA, 2012) of the Coruña Corpus the aim is to study nominalizations in the interface between cognition and language. The ultimate goal is to complement all the theoretical-descriptive studies on the topic by approaching the cognitive dimension and build a bridge for studies on the production and understanding of English scientific register.